1988
DOI: 10.1159/000309923
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Retinal Vein Occlusion and Its Association with Glaucoma and Increased Intraocular Pressure

Abstract: A population-based study found an overall incidence rate of symptomatic retinal vein occulusion (RVO) in a 4-year period to be 2.14 per 1,000 in the 40 years and over age group. When cases found among glaucoma clinic patients were separated from the remainder of the population there was marked difference in the incidence rate of RVO in the same time period (1.85 and 17.3 per 1,000, respectively). The rate of RVO increased significantly (p < 0.001) with age in the general population from 0.93 per 1,000 among pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
2
8

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 3 publications
3
103
2
8
Order By: Relevance
“…43 Elevated IOP and glaucoma have also been suggested as a cause for the association of XFS with CRVO. 24,26,44 Gillies et al 44 also found a strong agreement between the involved eye and the CRVO site in 10 patients with unilateral XFS, and attributed their findings to the higher IOP observed in the affected eyes. In our larger study, over 50% of the patients did not carry a diagnosis of glaucoma or ocular hypertension before developing RVO.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…43 Elevated IOP and glaucoma have also been suggested as a cause for the association of XFS with CRVO. 24,26,44 Gillies et al 44 also found a strong agreement between the involved eye and the CRVO site in 10 patients with unilateral XFS, and attributed their findings to the higher IOP observed in the affected eyes. In our larger study, over 50% of the patients did not carry a diagnosis of glaucoma or ocular hypertension before developing RVO.…”
Section: Discussionmentioning
confidence: 87%
“…[16][17][18][19][20][21][22][23] The pathogeneses and clinical features of acute retinal vascular occlusions (RVOs) are still not well understood. 24,25 Central retinal vein occlusion (CRVO) has been described in eyes with XFS, even when exfoliative glaucoma (XFG, a known risk factor) was not present. 26,27 As ocular involvement by XFS and XFG is often clinically unilateral or asymmetric, 7-12 the severity of ocular findings and its laterality could be associated with the side of occurrence of vascular occlusions.…”
Section: Introductionmentioning
confidence: 99%
“…The systemic medical and ophthalmic risk factors evaluated included those published in previous studies: hypertension, DM, hyperlipidemia, cardiovascular disease, smoking history, open-angle glaucoma, and elevated intraocular pressure (IOP). 7,[12][13][14][15][16][17][18][19][20][21] The ophthalmic findings from all patients at the initial (visit I), 4-month (visit M; window ¼ 3-6 months), and final follow-up (visit F) were recorded. Data from the visit prior to development of CRVO were also recorded when available (visit P).…”
Section: Methodsmentioning
confidence: 99%
“…11 Multiple systemic and ocular conditions are associated with CRVO. 7,[12][13][14][15][16][17][18][19][20][21] Many studies have confirmed higher prevalence of diabetes mellitus (DM) in patients with CRVO. 16,[21][22][23][24] Co-existing DM is reported in 10-34% of patients with CRVO and may affect the natural history in this subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Branch retinal vein occlusion (BRVO) is a frequent retinal vascular disease with an incidence of 2.14/1,000/ year in the population over 40 years of age (David et al 1988). It may cause immediate vision loss due to reduced blood perfusion and subsequent retinal hypoxia (Kanski 2007).…”
Section: Born Et Al 2005)mentioning
confidence: 99%